(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The research focuses on the essence of humanity, its meaning, people’s dreams, a journey on the way of Destiny created by God, and the outcomes and shortcomings of this journey by analyzing the life of protagonist in “Alchemist”. The main idea of this book is to present experiences of Santiago (the main character) who doesn’t afraid of doing something to achieve his dreams. The book says a person who started in a long journey (speaking in allegorical meaning) might search worldly wealth not comprehending that all worldly wealth is within him. Shortly, Alchemist explains not only the life of someone in the past, or the life of the protagonist of the legend - Santiago, but also it speaks the path that you are going to walk. The aim of the novel is to show the guideline for us and for those who come after us.